INVESTIGATION OF THE MELANIN INSTAPHYLOCOCCUS AUREUS ISOLATED FROM PATIENTS WITH URINARY TRACT INFECTIONS. - Al-Ameri, Kadhim H. A; Nasser, Ashjan Agar (International Journal of Current Innovations in Advanced Research, 2023)
The current study included isolating Staphylococcus aureus from the urine of men with urinary tract infections, where 17 isolates belonging to this species were obtained, which were diagnosed traditionally and by polymerase chain reaction. Then, the ability of the isolates to produce melanin was tested, as it is a substance that has great medical benefits, as it can be isolated and used as an antibacterial and antifungal, it has many other benefits. All isolates were melanin-producing, but the best of them were isolates 1, 2, 3and 10, which gave melanin amount of 3.1, 2.8, 3, and 2.9 mg/L, respectively, and gave a dry weight of 8.8, 6.5, and 6.1and 3.6 mg/l. Nitrogen sources gave close amounts of melanin, as follows: soybeans produced melanin with an amount of 2.7, yeast extract 2.6, and peptone 2.65 mg/l, while the best carbon sources culture medium was starch2.8 mg/l, then glucose came after that with 2.6 mg/l, then glycerol, maltose, fructose, sucrose, dextrose, and mannitol, with a yield of 2.4, 2.2, 2.2, 1.7, and 1.5 mg/l, respectively. The best temperature for melanin production was 35℃, followed by 30℃, then 25℃, then 40℃, then 20℃, with a melanin production amount of, 2.8, 2.3, 1.9, 1.7 and 1.1mgł respectively. As for the pH, the best was 7, followed by 6, then 8, followed by 5, then 4 with melanin amount of 2.7,2.2, 1.7,1.7 and 1.3 mg.